Effectiveness and cost-effectiveness of a universal parenting skills programme in deprived communities: multicentre randomised controlled trial. Issue 8 (1st August 2013) - Simkiss, D E; Snooks, H A; Stallard, N; Kimani, P K; Sewell, B; Fitzsimmons, D; Anthony, R; Winstanley, S; Wilson, L; Phillips, C J; Stewart-Brown, S
Abstract : Objective: To evaluate the effectiveness and cost utility of a universally provided early years parenting programme. Design: Multicentre randomised controlled trial with cost-effectiveness analysis. Setting: Early years centres in four deprived areas of South Wales. Participants: Families with children aged between 2 and 4 years. 286 families were recruited and randomly allocated to the intervention or waiting list control. Intervention: The Family Links Nurturing Programme (FLNP), a 10-week course with weekly 2 h facilitated group sessions. Main outcome measures: Negative and supportive parenting, child and parental well-being and costs assessed before the intervention, following the course (3 months) and at 9 months using standardised measures. Results: There were no significant differences in primary or secondary outcomes between trial arms at 3 or 9 months. With '+' indicating improvement, difference in change in negative parenting score at 9 months was +0.90 (95%CI −1.90 to 3.69); in supportive parenting, +0.17 (95%CI −0.61 to 0.94); and 12 of the 17 secondary outcomes showed a non-significant positive effect in the FLNP arm. Based on changes in parental well-being (SF-12), the cost per quality-adjusted life year (QALY) gained was estimated to be £34 913 (range 21 485–46 578) over 5 years and £18 954 (range 11 664–25 287) over 10 years. Probability of cost per QALY gained below £30 000 was 47% at 5 years and 57% at 10 years. Attendance was low: 34% of intervention families attended no sessions (n=48); only 47% completed the course (n=68). Also, 19% of control families attended a parenting programme before 9-month follow-up. Conclusions: Our trial has not found evidence of clinical or cost utility for the FLNP in a universal setting. However, low levels of exposure and contamination mean that uncertainty remains. Trial registration: The trial is registered with Current Controlled Trials ISRCTN13919732 .